First International Conference on RASopathies and Neurofibromatoses in Asia: Identification and advances of new therapeutics. Issue 6 (25th March 2019) - Rauen, Katherine A.; Alsaegh, Abeer; Ben‐Shachar, Shay; Berman, Yemima; Blakeley, Jaishri; Cordeiro, Isabel; Elgersma, Ype; Evans, D. Gareth; Fisher, Michael J.; Frayling, Ian M.; George, Joshi; Huson, Susan M.; et al.
Abstract : The neurofibromatoses, which include neurofibromatosis type I (NF1), neurofibromatosis type II (NF2), and schwannomatosis, are a group of syndromes characterized by tumor growth in the nervous system. The RASopathies are a group of syndromes caused by germline mutations in genes that encode components of the RAS/mitogen‐activated protein kinase (MAPK) pathway. The RASopathies include NF1, Noonan syndrome, Noonan syndrome with multiple lentigines, Costello syndrome, cardio‐facio‐cutaneous syndrome, Legius syndrome, capillary malformation arterio‐venous malformation syndrome, and SYNGAP1 autism. Due to their common underlying pathogenetic etiology, all these syndromes have significant phenotypic overlap of which one common feature include a predisposition to tumors, which may be benign or malignant. Together as a group, they represent one of the most common multiple congenital anomaly syndromes estimating to affect approximately one in 1000 individuals worldwide. The subcontinent of India represents one of the largest populations in the world, yet remains underserved from an aspect of clinical genetics services. In an effort to bridge this gap, the First International Conference on RASopathies and Neurofibromatoses in Asia: Identification and Advances of New Therapeutics was held in Kochi, Kerala, India. These proceedings chronicle this timely and topical international symposium directed at discussing the best practices and therapies for individuals with neurofibromatoses and RASopathies.